Dark heritage tourism and the Sarajevo siege. Issue 3 (2nd July 2016) - Kamber, Marija; Karafotias, Theofanis; Tsitoura, Theodora
ABSTRACT: Sarajevo bears a rich and diverse cultural past, which includes the three distinct periods of the Ottoman occupation (1463–1878), the Austro–Hungarian rule (1878–1914) and the Yugoslav Federation (1945–1989). But the darkest chapter in its long history was about to be written just after Bosnia and Herzegovina was recognized as an independent country in 1992, when the latest war of 1992–1995 unfolded. One of the most distinctive episodes of that war was the siege of Sarajevo. Apart from the open wounds, the Sarajevo siege left behind a painful heritage too. As a matter of course, the goal of this paper is to try to answer some of the crucial questions related to the management of the 1992–1995 war sites in Sarajevo. In our research, we investigate tourists' motives and expectations for visiting these sites as well as to identify crucial issues in managing 'dark tourism/heritage' sites. Moreover, the paper provides an analysis that could be a powerful tool for the different stakeholders to design activities and promote and manage effectively the war-related sites in Sarajevo, depending on the needs and opinion of their public.